Comparative changes in psychological mindedness, mindfulness, and concordance attitudes between online and face-to-face undergraduate psychiatry education in a university in Borneo, Malaysia - Pang, Nicholas Tze Ping; Mohd Amiruddin Mohd Kassim; Shoesmith, Wendy Diana; James, Sandi (Penerbit UMS, 2021)
Introduction: Psychiatry posting is one of essential posting for medical students in Universiti Malaysia Sabah. Apart from learning about mental health disorder, students are also exposed to various psychotherapies techniques are crucial in psychiatric practise. However, in view of COVID-19, online learning had to be adopted, instead of the traditional face-to-face learning. Methods: The study aimed to assess the difference in diverse psychological constructs, such as psychological mindedness, flexibility, and mindfulness; pre- & post-psychiatry posting, and to determine whether online learning was comparable to face-to-face learning. The study was done on 58 undergraduate medical student populations, utilizing a set of scales to determine the psychological constructs, viz., balanced Index of psychological mindedness, Leeds attitudes to Concordance Scale II (LATCon II), the mindful attention awareness scale, and the acceptance and action questionnaire-II, which were administered before & after completion of the posting. Results: Results were subsequently analysed using IBM SPSS. Interestingly, both control group (mean difference= 15.155, p= 0.004) and online psychiatry posting (mean difference 12.691, p= 0.014) had higher mindfulness level when compared to face-to-face psychiatry posting. Despite the common perception that psychiatry posting raises awareness regarding mental health, it was found that there were no significant differences in psychological constructs pre- and post-psychiatry posting. Interestingly, the online psychiatry posting also found to be as effective as the face-to-face psychiatry posting. Conclusion: This study highlighted the applicability of online learning in psychiatry, which could be crucial in maintaining continuity of learning during these uncertain times.